Apoptosis induction, cell cycle arrest and in vitro anticancer activity of gonothalamin in a cancer cell lines - Alabsi, A.M.; Ali, R.; Ali, A.M.; Al-Dubai, S.A.R.; Harun, H.; Abu Kasim, N.H.; Alsalahi, A. (2012)
Cancer is one of the major health problems worldwide and its current treatments have a number of undesired adverse side effects. Natural compounds may reduce these. Currently, a few plant products are being used to treat cancer. In this study, goniothalamin, a natural occurring styryl-lactone extracted from Goniothalamus macrophyllus, was investigated for cytotoxic properties against cervical cancer (HeLa), breast carcinoma (MCF-7) and colon cancer (HT29) cells as well as normal mouse fibroblast (3T3) using MTT assay. Fluorescence microscopy showed that GTN is able to induce apoptosis in HeLa cells in a time dependent manner. Flow cytometry further revealed HeLa cells treated with GTN to be arrested in the S phase. Phosphatidyl serine properties present during apoptosis enable early detection of the apoptosis in the cells. Using annexin V/PI double staining it could be shown that GTN induces early apoptosis on HeLa cells after 24, 48 and 72 h. It could be concluded that goniothalamin showing a promising cytotoxicity effect against several cancer cell lines including cervical cancer cells (HeLa) with apoptosis as the mode of cell death induced on HeLa cells by Goniothalamin was.